1991
DOI: 10.1111/j.1469-8986.1991.tb01999.x
|View full text |Cite
|
Sign up to set email alerts
|

Fear‐Potentiated Startle in Humans: Effects of Anticipatory Anxiety on the Acoustic Blink Reflex

Abstract: The effects of fear/anticipatory anxiety on the acoustic startle reflex were investigated in humans using a paradigm involving anticipation of electric shocks. The eyeblink component of the startle reflex, elicited by an abrupt auditory stimulus, was measured in 9 normal volunteers during either the anticipation of electric shocks (anticipatory anxiety) or periods in which no shocks were anticipated (safe period). The eyeblink was consistently higher in amplitude, and shorter in latency, during periods when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
324
4
4

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 418 publications
(356 citation statements)
references
References 42 publications
24
324
4
4
Order By: Relevance
“…Subjects were instructed of the contingency between the shock and the threat cue, and instructions concerning the various threat conditions were clearly displayed on the monitor facing the subjects throughout testing (See Methods). Prior studies with this paradigm show that threat cues are very easy to discriminate from safe cues (Grillon et al, 1991). The findings also cannot be due to enhanced recognition of the threat signal because fear was probed with the startle reflex several seconds after cue onset, leaving subjects ample time to recognize the non-ambiguous threat cue.…”
Section: Discussionmentioning
confidence: 87%
“…Subjects were instructed of the contingency between the shock and the threat cue, and instructions concerning the various threat conditions were clearly displayed on the monitor facing the subjects throughout testing (See Methods). Prior studies with this paradigm show that threat cues are very easy to discriminate from safe cues (Grillon et al, 1991). The findings also cannot be due to enhanced recognition of the threat signal because fear was probed with the startle reflex several seconds after cue onset, leaving subjects ample time to recognize the non-ambiguous threat cue.…”
Section: Discussionmentioning
confidence: 87%
“…An alternative to conditioning is verbal instructions in which the time of US administration is verbally communicated rather than learned via experience (Grillon et al 1991). Verbal instructions experiments mimic the mode of communication of danger typically involved in everyday human life without directly experiencing the aversive event (e.g., one learns to fear an electrical outlet, not because one has been electrocuted, but because one has been forewarned of the risk).…”
Section: Verbal Instructionsmentioning
confidence: 99%
“…Supporting this idea, the amygdala, a key structure implied in fear responses, plays a critical role in the evocation of the fearpotentiated startle reflex 21,39,46,60,61 . Furthermore, research on personal pain experience has consistently shown that participants display a fear-potentiated startle when experiencing or 18 anticipating pain 25,38,41,47 , particularly when pain is perceived as highly threatening 7 Observers' distress towards pain signals in others likely serve a protective function of preparing observers for dealing with impending threat 40 . Specifically, observers' distress responses may instigate avoid/escape tendencies 72,81 .…”
Section: Self-report Datamentioning
confidence: 99%
“…Through first-hand experiences, we learn to predict pain, and these signals for pain may in themselves become a source of fear and action 1,7,29,38,75 . However, pain is rarely a private event as the sufferer's reactions to pain have the capacity to communicate pain to others 40 .…”
Section: Introductionmentioning
confidence: 99%